To evaluate the efficacy and safety of "RV2427B" cream in Irritant dermatitis care - Ramesh M Bhat; Rajeev Chavda; Virginie Ribet (Wolters Kluwer Medknow Publications, 2013)
Background: The treatment of various irritant dermatitis involves the elimination of the casual or favoring factor, the control of aggravating factors, and administration of topical agents. Even though corticosteroids are extensively used in these conditions to reduce the inflammation, it can also result in undesirable side effects. Hence, there is a need for a non steroidal topical agent to be used in these conditions. Aims: To evaluate the efficacy and tolerance of repairing cream "RV 2427B" in children and adults in irritant dermatitis care. Materials and Methods: In this phase III open labeled, multicenter, non-controlled, non-randomized trial, irritant dermatitis in children and adults either due to diaper rash, pityriasis alba and irritant dermatitis (eczema), perioral dermatitis, perleche or intertrigo were administered; repairing cream RV 2427 B containing a) 4 % zinc oxide, b) 2.5 % dry colloidal oat extract, (c) 0.5 % oat oil, (d) 0.2% copper sulfate, and (e) 0.1 % zinc sulfate to be applied twice-daily in the affected area. The subjects were evaluated on day 7 and day 21 for both efficacy and tolerance and last visit for cosmetic acceptability. The trial was conducted in accordance with the good clinical practices (GCP) after obtaining ethical clearance from respective Institutional Review Boards. Statistical evaluation was by variance analysis and student test for the quantitative variables, chi-square test for the qualitative variables. Results: Of the 136 enrolled subjects, 95 completed the study. After 21 days of treatment, 84% of the subjects assessed by the investigator and 76% by the self-assessment for the cream found effective. Investigational product was considered to be safe after 7 and 21 days of use. Conclusion: Repairing cream "RV 2427 B" is effective and safe in the management of irritant dermatitis.